Distribution and turnover of carbon in natural and constructed wetlands in the Florida Everglades - Stern, J.; Wang, Y.; Gu, B.; Newman, J. (Applied Geochemistry, 2007)
Stable and radiocarbon isotopic contents of dissolved organic C (DOC), dissolved inorganic C (DIC), particulate organic C (POC) and plants were used to examine the source and turnover rate of C in natural and constructed wetlands in the Florida Everglades. DOC concentrations decreased, with P concentrations, along a water quality gradient from the agriculturally impacted areas in the northern Everglades to the more pristine Everglades National Park. delta C-13 values of DOC in the area reflect contributions of both wetland vegetation and sugarcane from agriculture. Radiocarbon ages of DOC, POC and DIC in the Everglades ranged from 2.01 ka BP to ">modern". The old C-14 ages of DOC and POC were found in impacted areas near the Everglades Agricultural Area (EAA) in the northern Everglades. In contrast, DOC and POC in pristine marsh areas had near modern or ">modern" C-14 ages. These data indicate that a major source of POC and DOC in impacted areas is the degradation of historic peat deposits in the EAA. In the pristine areas of the marsh, DOC represents a mix of modern and historic C sources, whereas POC comes from modern primary production as indicated by positive A C-14 values, suggesting that DOC is transported farther away from its source than POC. High A C-14 values of DIC indicate that dissolution of limestone bedrock is not a significant source of DIC in the Everglades wetlands. As a restored wetland moves towards its "original" or "natural" state, the C-14 signatures of DOC should approach that of modern atmosphere. In addition, measurements of concentration and C isotopic composition of DOC in two small constructed wetlands (i.e., test cells) indicate that these freshwater wetland systems contain a labile DOC pool with rapid turnover times of 26-39 days and that the test cells are overall net sinks of DOC. (C) 2007 Elsevier Ltd. All rights reserved.
216vhTimes Cited:23Cited References Count:36